Waste tracker system / Siti Suhaili Amir Hamzah and Siti Akhtar Mahayuddin - Amir Hamzah, Siti Suhaili; Mahayuddin, Siti Akhtar (2023)
The Waste Tracker System in construction dumpsters represents a transformative solution for revolutionising waste management practices at construction sites. This innovative system seamlessly integrates with existing conventional dumpsters while incorporating advanced technology to optimise waste tracking, segregation, and disposal efficiency. Real-time monitoring of waste fill levels enables construction managers and project supervisors to make informed decisions, optimising waste collection schedules and reducing operational costs. The interior of the dumpster is intelligently equipped with the Waste Tracker System, allowing for efficient waste segregation, identification of recyclable materials, and increased recycling rates. By promoting responsible waste disposal practices, the system contributes to improved environmental sustainability, aligning with green building initiatives and regulatory requirements.